Flexibility in electricity wholesale markets and distribution grids: An integrated model and its application to electric vehicles in Germany - Arne Lilienkamp; Nils Namockel; Oliver Ruhnau (Institute of Energy Economics at the University of Cologne (EWI), 2025)
The ongoing transition of our energy systems implies a rise of distributed generators, batteries, and new consumers, including electric vehicles and heat pumps. Previous studies have found that distributed flexibility may substantially benefit wholesale electricity markets, but have neglected that these benefits may be subject to distribution grid constraints. Here, we propose using a virtual storage approach to aggregate the net load and flexibility of individual consumers at the distribution grid level, subject to the corresponding grid constraints. We apply our approach to flexible electric vehicle charging scenarios in German distribution grids for the years 2030 and 2045. Our results suggest that distributed flexibility exacerbates distribution grid congestion if it only follows wholesale market prices. However, there may be the potential to allevi- ate local congestion with stable wholesale market benefits of distributed flexibility. Local coordination of distributed flexibility appears to be able to resolve distribution grid constraints at substantially lower costs than expanding transformer capacity. We conclude that local coordination mechanisms are key to unlocking the wholesale market benefits of distributed flexibility while mitigating hazards in the distribution grids.
Keywords: C61; D47; Q21; Q41; Q48; 330; Electric vehicles; Distribution grids; Energy system modeling; Flexibility; Grid expansion